Dichloro Butenediamides as Irreversible Site‐Selective Protein Conjugation Reagent. (29th September 2021) - Laserna, Victor; Abegg, Daniel; Afonso, Cláudia F.; Martin, Esther M.; Adibekian, Alexander; Ravn, Peter; Corzana, Francisco; Bernardes, Gonçalo J. L.
Abstract: We describe maleic‐acid derivatives as robust cysteine‐selective reagents for protein labelling with comparable kinetics and superior stability relative to maleimides. Diamide and amido‐ester derivatives proved to be efficient protein‐labelling species with a common mechanism in which a spontaneous cyclization occurs upon addition to cysteine. Introduction of chlorine atoms in their structures triggers ring hydrolysis or further conjugation with adjacent residues, which results in conjugates that are completely resistant to retro‐Michael reactions in the presence of biological thiols and human plasma. By controlling the microenvironment of the reactive site, we can control selectivity towards the hydrolytic pathway, forming homogeneous conjugates. The method is applicable to several scaffolds and enables conjugation of different payloads. The synthetic accessibility of these reagents and the mild conditions required for fast and complete conjugation together with the superior stability of the conjugates make this strategy an important alternative to maleimides in bioconjugation. Abstract : Maleic acid derivatives are studied as cysteine‐selective reagents for protein labelling with comparable kinetics and superior stability to existing reagents. A novel mechanism is described to readily access stable chloro‐maleamic acid. The mild conditions, fast kinetics, and irreversible conjugation make this method an appealing alternative to existing cysteine‐targeted methods.